1997
DOI: 10.1002/(sici)1097-0134(199708)28:4<530::aid-prot7>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

On the reaction mechanism of class Pi glutathione S-transferase

Abstract: Theoretical calculations were performed to examine the ionization of the phenolic group of Tyr7 and the thiol group of glutathione in aqueous solution and in the protein class-pi glutathione S-transferase (GST-Pi). Three model systems were considered for simulations in the protein environments the free enzyme, the complex between glutathione and the enzyme, and the complex between 1-chloro-2.4-dinitrobenzene, glutathione, and the enzyme. The structures derived from Molecular Dynamics simulations were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…This gives an indication of the nature of the active site at various points during the reaction. Molecular dynamic studies have suggested that GS − is stabilized by the OH group of Y7 (tyrosine) and the water molecules W1, W2 and W4, and is consistent with a model whereby the proton from glutathione is initially displaced onto water molecule W0 [38,39]. The structure of the C47A mutant of mGSTP1‐1 complexed with S‐ ( p ‐nitrobenzyl)glutathione presented here reveals an intriguing difference in alignment of the inhibitor at the two sites.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This gives an indication of the nature of the active site at various points during the reaction. Molecular dynamic studies have suggested that GS − is stabilized by the OH group of Y7 (tyrosine) and the water molecules W1, W2 and W4, and is consistent with a model whereby the proton from glutathione is initially displaced onto water molecule W0 [38,39]. The structure of the C47A mutant of mGSTP1‐1 complexed with S‐ ( p ‐nitrobenzyl)glutathione presented here reveals an intriguing difference in alignment of the inhibitor at the two sites.…”
Section: Resultssupporting
confidence: 81%
“…In addition, the water channel identified in human GSTP1 [41] and rat, rattus norvegicus GSTA1 [42] as connecting the two active sites of the dimer may also play a functional role in the observed cooperativity. Finally, there have been a number of suggestions as to the ultimate proton sink, including a channel filled by four water molecules, which passes between helices αA and αF and reaches the solvent at R11 [32], the α‐carboxylate of the γ‐glutamyl residue of GSH [43], or simply extrusion of W0 [38,39].…”
Section: Resultsmentioning
confidence: 99%